Increased EZH2 expression in prostate cancer is associated with metastatic recurrence following external beam radiotherapy. Issue 10 (18th May 2019) - Wu, Xiaoning; Scott, Helen; Carlsson, Sigrid V.; Sjoberg, Daniel D.; Cerundolo, Lucia; Lilja, Hans; Prevo, Remko; Rieunier, Guillaume; Macaulay, Valentine; Higgins, Geoffrey S.; Verrill, Clare L.; Lamb, Alastair D.; et al.
Abstract: Background: Enhancer of zeste 2 (EZH2) promotes prostate cancer progression. We hypothesized that increased EZH2 expression is associated with postradiotherapy metastatic disease recurrence, and may promote radioresistance. Methods: EZH2 expression was investigated using immunohistochemistry in diagnostic prostate biopsies of 113 prostate cancer patients treated with radiotherapy with curative intent. Associations between EZH2 expression in malignant and benign tissue in prostate biopsy cores and outcomes were investigated using univariate and multivariate Cox regression analyses. LNCaP and PC3 cell radiosensitivity was investigated using colony formation and γH2AX assays following UNC1999 chemical probe‐mediated EZH2 inhibition. Results: While there was no significant association between EZH2 expression and biochemical recurrence following radiotherapy, univariate analysis revealed that prostate cancer cytoplasmic and total EZH2 expression were significantly associated with metastasis development postradiotherapy ( P = 0.034 and P = 0.003, respectively). On multivariate analysis, the prostate cancer total EZH2 expression score remained statistically significant ( P = 0.003), while cytoplasmic EZH2 expression did not reach statistical significance ( P = 0.053). No association was observed between normal adjacent prostate EZH2 expression and biochemical recurrence or metastasis. LNCaP and PC3 cell treatment with UNC1999 reduced histone H3 lysine 27 tri‐methylation levels. Irradiation of LNCaP or PC3 cells with a single 2 Gy fraction with UNC1999‐mediated EZH2 inhibition resulted in a statistically significant, though modest, reduction in cell colony number for both cell lines. Increased γH2AX foci were observed 24 hours after ionizing irradiation in LNCaP cells, but not in PC3, following UNC1999‐mediated EZH2 inhibition vs controls. Conclusions: Taken together, these results reveal that high pretreatment EZH2 expression in prostate cancer in diagnostic biopsies is associated with an increased risk of postradiotherapy metastatic disease recurrence, but EZH2 function may only at most play a modest role in promoting prostate cancer cell radioresistance.